Analisis Sektor Ekonomi Potensial Pendorong Kemajuan Ekonomi Sumatera - Febriyani, Ananda; Iskandar, Dadang Ishak; Mervita, Eda; Rumianti, Susti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Even though inter-island trade is important and Sumatra is Indonesia's second largest economy, Sumatra imports more from other islands in Indonesia than exports. This research will be carried out descriptively to determine the trade structure of the island of Sumatra with other islands in Indonesia and potential sector purchases in downstream. This study uses secondary data published by the Central Bureau of Statistics (BPS). The secondary data used is the input-output data table between Indonesian regions, domestic transactions based on producer prices according to 6 island groups and 17 business fields in 2016. The results of this study indicate that trade between Sumatra and other islands suffers a slight loss because there are more imports from other islands. compared to export output by Sumatra. The use of output from the island of Sumatra is almost balanced between final demand and intermediate demand. The majority of Sumatra's output circulates in the Sumatra region only. Sumatra trade interaction is dominant with the island of Java. From a sector perspective, the majority of Sumatra's exports come from the manufacturing sector as well as the sector with the largest output value. Even though it has the largest output value, this sector is the most powerful in driving progress in the upstream sector. As for downstream, the Electricity and Gas Procurement sector has the greatest potential in terms of impacting progress on the downstream sector. Keywords : Economic Sector, IRIO, Inter-Island Trade.